Alvarado score: a guide to computed tomography utilization in appendicitis. Issue 10 (27th January 2013) - Tan, Winson Jianhong; Pek, Wansze; Kabir, Tousif; Goh, Yaw Chong; Chan, Weng Hoong; Wong, Wai Keong; Ong, Hock Soo
Abstract Background Although useful in evaluation of suspected appendicitis, not all patients require computed tomography (CT) evaluation. Clinical stratification of patients who benefit from CT evaluation is essential. We utilize the Alvarado score (AS) to stratify patients with suspected appendicitis into subgroups who benefit from CT evaluation and propose an objective algorithm with AS guiding CT utilization. Methods This study is a retrospective review of medical records of all patients admitted for suspected appendicitis over a 6‐month duration. Relevant data were recorded. The AS for each patient was determined retrospectively and correlated with histological and CT findings. The sensitivity, specificity, positive predictive value (PPV) and negative predictive value (NPV) were determined for various ASs and for CT. Results Three hundred fifty‐eight patients were studied, with 167 males (46.6%) and 191 females (53.4%). Prevalence of appendicitis was 50% (179 patients). Two hundred fourteen patients (59.8%) had CT performed. Surgery was performed for 206 patients (57.5%). Overall negative appendicectomy rate was 13.1%. Patients who underwent CT evaluation had a negative appendicectomy rate of 5.7% compared to 17.9% in those without CT evaluation (P = 0.009). CT scan had a sensitivity and specificity of 92.6% and 96.9%, respectively. An AS greater than 3 had a sensitivity superior to CT (95.5%), while an AS of 9 or greater had a specificity superior to CT (100%). Conclusions In suspected appendicitis, patients who benefit from CT evaluation are those with the AS ranging from 4 to 8. We propose a management algorithm with the AS guiding the necessity for CT evaluation.